Perceptions about UBER-TAXIS conflict in Costa Rica - Rodríguez Soto, Maritza (2021)
This article is about the conflict that arises in the country, since the Uber platform began operations in 2015, between the drivers of this application and the drivers of regular taxis. This conjuncture has allowed us to analyze this phenomenon from different angles, such as: the development of technological applications as part of the capitalist development dynamics, which disconnect the employer figure from the population that exercises this job, labor precarization and its implications in what respects labor rights, the effects that Covid 19 has generated in Uber collaborators, and the lack of regulation by the Costa Rican State regarding the operation of people transportation services companies through technological applications. The sources of information used for this analysis are based on the Perception survey on aspects of the situation and political cultures in Costa Rica 2018, by the IDESPO-UNA, Umbral Político Program, applied to a sample of 1003 people at the national level, by cell phone; In addition, two interviews were conducted with Uber drivers, a review of news in the media regarding the conflict, and a review of the bills presented by the Executive Power before the Costa Rican Legislative Assembly, for the regulation of this type of transportation services of people in the country, as well as other documentation related to these files.